Does jejunal feeding promote growth in children with worsening upper GI dysmotility?. (24th May 2012) - Paxton, CE; Robb, V; Livingstone, J; Wilson, DC
Abstract : Background and aim: Promotion of optimal growth and development in children with underlying chronic disease is a goal of nutrition support teams (NST). NST are faced with a challenging group of children (usually with profound underlying neurodisability) in whom worsening upper GI dysmotility limits feed toleration and impacts growth. Jejunal feeding is increasingly used in this group when changes in feed type, method of feed delivery and maximal medical management of reflux have all failed to promote growth. We aimed to evaluate the effect of jejunal feeding on subsequent growth in children with severe GI dysmotility. Methods: A retrospective cohort study (database/clinical note review) in a tertiary paediatric centre to investigate the impact on growth of jejunal feeding (>6 months) in children with worsening GI dysmotility. All children (<18 years) receiving home enteral tube feeding (HETF) during the period 01.01.02-30.09.11 were included. Data on weight at time of commencing jejunal feeding and at 6 or 12 months (whichever duration was exceeded) post establishment was collected and expressed as standard deviation or Z-score. Change in Z-score was calculated using paired t-test. Results: A total of 866 children received HETF during the study period, of whom 38 (4%) were jejunally fed. Growth data was collected on 25 (56% female) children fed via a transgastric gastrojejunostomy (GJ) tube, PEG-J or a surgical roux-en Y jejunostomy >6 months. Median (range) decimal age at commencement of jejunal feeding was 2.6 (0.1-16.2) years. The median (range) weight Z-score at the start of jejunal feeding was –1.3 (−5.2 to 2.1) and rose to –1.0 (−3.4-2.3) by 6-12 months post-start. A significant improvement in mean (95% CI) change in weight Z-score of 0.7 (0.1-1.3) (p=0.02) was found. As the majority of children were non-ambulatory (and knee heights are not routinely recorded), there was minimal height (and thus BMI) data recorded. Children received a range of jejunal feed types - 42% whole protein, 41% hydrolysed and 17% elemental feeds. Conclusions: Jejunal feeding is an effective intervention to improve growth during the management of children with severe and worsening upper GI dysmotility on HETF.